Music technology in live performance : tools, techniques, and interaction - Canfer, Tim (New York, NY : Routledge, 2024)
"Music Technology in Live Performance explores techniques to augment live musical performance and represents a comprehensive guide to best practices in music technology for live performance. This book presents a practical and accessible introduction to the theories of liveness and an array of live performance technologies and techniques. Areas covered include analogue and digital audio, live sound, the recording studio, and electronic music, revealing best professional practices and expert tips, alongside an exploration of approaches to increasing the exchange of energy in live performance. Music Technology in Live Performance is an ideal introduction for students of music performance, music production and music technology, and a vital resource to professional musicians, producers, and technology developers"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Music -- Performance; Computer sound processing; Concerts -- Production and direction; Electronic music -- Production and direction